Mapping small burned areas using high spatial resolution planetscope imagery: a case study of the wildfire in Da Lat city - Duc Binh, Pham (Journal of Forestry Science and Technology, 2023)
This study employed high spatial resolution PlanetScope imagery at 3 m resolution for mapping burned area and burn severity resulting from a wildfire that occurred from April 7-9, 2023 in the highland of Vietnam. The wildfire took place in a protection forest near the Prenn pass in Da Lat city, Lam Dong province, Vietnam. Pre- and post-fire Normalized Difference Vegetation Index (NDVI) maps were generated using no-cloud high-resolution images acquired on March 25 and April 23, 2023 by the PlanetScope’s SuperDove satellites, respectively. The difference of NDVI (dNDVI) was then calculated, and thresholds, proposed by the author, were utilized to classify the study area into three different classes: unburned, low-to-moderate and high severity. The results showed that the total burned area was approximately 13.86 ha, with 8.19 ha classified as low-to-moderate severity, and 5.68 ha classified as high severity. Although there was no reference dataset to cross-validate the results, the estimated burned area is very close to the total affected area officially reported by the Forest Protection Department of Lam Dong province (about 13 ha). This study is one of the few that investigates the use of high-resolution PlanetScope imagery for environmental monitoring in Vietnam, and the first to focus on burned area and burn severity mapping in Vietnam. This work demonstrates the potential of PlanetScope images for mapping burned area and burn severity, particularly in small regions where other optical satellites, such as Sentinel-2 and Landsat, may not provide accurate results due to their spatial resolution limitations.